Ionic liquid-based modified polyimide nanofiber film and air purification filter screen based on ionic liquid-based modified polyimide nanofiber film
By adding ionic liquid to the polyamic acid spinning liquid and subjecting electrospinning and thermal imidation treatment, a modified polyimide nanofiber membrane was prepared, which solved the problems of low filtration efficiency and large resistance of the polyimide nanofiber membrane, and achieved more efficient air filtration performance.
Patent Information
- Application Number
- CN202411904786.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-02-28
AI Technical Summary
Polyimide nanofiber membranes have low filtration efficiency and high filtration resistance during air filtration, making it difficult to efficiently filter charged particulate matter in the air.
By adding ionic liquid to the polyamic acid spinning liquid, modifying polyimide nanofiber films, using electrospinning technology to prepare nanofiber films, and undergoing thermal imidation treatment to form nanofiber films with improved filtration performance.
The filtration efficiency and physical adsorption capacity of nanofiber membranes in air filtration are improved, the filtration resistance is reduced, and the ability to capture fine particles is enhanced.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of film filter material development, and relates to an ionic liquid-modified polyimide nanofiber film and an air purification filter based thereon. Background Art
[0002] With the rapid development of industrialization and urbanization, a large amount of pollutants emitted from industry, transportation and daily life will enter the air, making air pollution more serious. Pollutants in the atmosphere mainly include harmful gases and particulate matter. Suspended particulate matter pollution (PMs) has become one of the main factors endangering air quality and human life and health. Among them, PM 2.5 It can penetrate the respiratory tract, alveolar tissue, etc. and remain in the body, seriously endangering human health. Since PMs are produced in a high temperature environment, a filter material with good thermal stability is needed to filter and purify PMs at the source of production. The nanofiber membrane filter material prepared by electrospinning technology has the advantages of small pore size (150~500nm), high porosity and large specific surface area, and is an excellent air filtration material. It is very effective in filtering high-temperature and small-sized particles (PM 2.5 、PM 0.3 ) industrial waste gas, electrospinning nanofiber membranes play an extremely important role and have gradually been used in the field of high-precision air filtration in recent years.
[0003] Polyimide (PI) is a type of polymer with an imide ring in the main chain and an aromatic heterocyclic structure. It is one of the organic polymer materials with the best comprehensive performance, and has excellent properties such as high strength and modulus, corrosion resistance, radiation resistance, flame retardancy, excellent thermal stability, and low dielectric constant. More importantly, polyimide is a polymer material with the highest heat resistance level and is an ideal matrix material for high-temperature resistant filter materials. The polyimide nanofiber membrane prepared based on electrospinning technology has a three-dimensional network structure with a large number of interconnected pores inside. In addition, a certain charge is given to the nanofiber material during the spinning process. It has the characteristics of high specific surface area and strong ability to capture fine particles, making it an excellent material for air filtration and purification. However, the single polyimide nanofiber membrane has weak electrostatic adsorption ability, cannot efficiently filter charged particles in the air, and has a large filtration resistance, resulting in poor filtration performance for fine charged particles. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a polyimide nanofiber film modified by ionic liquid and an air purification filter based thereon, thereby solving the technical problems in the prior art that the polyimide nanofiber membrane has low filtration efficiency and high filtration resistance when performing air filtration.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a polyimide nanofiber film modified by an ionic liquid comprises the following steps: S1: mixing a diamine monomer and a dianhydride monomer to react to obtain a polyamic acid solution, performing solvent replacement and freeze drying to obtain a polyamic acid powder; S2: dissolving the polyamic acid powder in a polar solvent to obtain a polyamic acid spinning solution, and then adding an ionic liquid and stirring evenly to obtain an ionic liquid / polyamic acid spinning solution; S3: using the ionic liquid / polyamic acid spinning solution to perform electrospinning to obtain an ionic liquid / polyamic acid nanofiber membrane; S4: performing thermal imidization treatment on the ionic liquid / polyamic acid nanofiber membrane to obtain the ionic liquid modified polyimide nanofiber film.
[0006] Preferably, in step S1, the molar ratio of the diamine monomer to the dianhydride monomer is (0.95-1):(1-1.05); during the mixed reaction of the diamine monomer and the dianhydride monomer, the reaction temperature is 0-4° C. and the reaction time is 24-28 h.
[0007] Preferably, in step S1, the solvent replacement is specifically: slowly pouring the polyamic acid solution into water to solidify, and washing it multiple times to complete the solvent replacement process.
[0008] Preferably, in step S2, the polar solvent is at least one of N,N'-dimethylformamide, N,N'-dimethylacetamide, N-methylpyrrolidone and tetrahydrofuran.
[0009] Preferably, the ionic liquid is one of 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate and 1-butyl-3-methylimidazolium hexafluorophosphate.
[0010] Preferably, after adding the ionic liquid, the mass concentration ratio of the ionic liquid to the polyamic acid spinning solution is (0.25%~1%):(36%~40%).
[0011] Preferably, during the electrospinning process, the spinning voltage is 16 kV to 18 kV, the flow rate of the spinning solution is 0.010 to 0.015 ml / min, and the distance between the needle and the receiving roller is 15 to 20 cm.
[0012] Preferably, the thermal imidization treatment is specifically as follows: heating to 150-170°C at a heating rate of 5°C / min, keeping warm for 30-60 min, then heating to 250-270°C at a heating rate of 5°C / min, keeping warm for 30-60 min, and finally heating to 300-320°C at a heating rate of 5°C / min, keeping warm for 30-60 min.
[0013] A polyimide nanofiber film modified by ionic liquid is prepared by the above method, wherein the average diameter of the polyimide nanofiber modified by ionic liquid is 200-350 nm; the average pore size of the polyimide nanofiber film modified by ionic liquid is 10-25 nm; the quality factor of the polyimide nanofiber film modified by ionic liquid is 0.022-0.74 Pa -1 .
[0014] An air purification filter comprises the above-mentioned ionic liquid-modified polyimide nanofiber film.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: A preparation method of a polyimide nanofiber film modified by an ionic liquid, wherein the spinning state of the polyamic acid spinning solution in the electrostatic spinning process is improved by adding an ionic liquid to the polyamic acid spinning solution. When electrostatic spinning is performed without adding an ionic liquid, nanofibers with the same charge (positive charge) repel each other, the fibers are separated from each other, and the jet is longer, and the stretching time of the nanofibers in the electrostatic field is shorter, resulting in a larger fiber diameter. After the ionic liquid is added to the spinning solution, the negative charge will remain in the fiber due to the attraction of the positive charge during the electrostatic spinning process, forming some nanofibers with excess negative charge. These negatively charged nanofibers will contact and bond with some positively charged nanofibers near a needle tip. As the content of the ionic liquid increases, the jet will get closer to the needle tip, causing the jet to shorten, which will extend the stretching time of the nanofibers in the electrostatic field, thereby reducing the diameter of the nanofibers. At the same time, the advantages of ionic liquids are low vapor pressure, high boiling point, high conductivity and wide electrochemical window, and also high thermal stability and chemical stability, strong designability, and different chemical structures and properties can be designed according to different needs; non-flammable, odorless, recyclable, and green and friendly. That is, the scheme uses the advantages of high ionic conductivity of ionic liquids to make the polyamic acid spinning solution carry more charges, thereby increasing the conductivity of the spinning solution, making the fiber more strongly stretched in the electric field, effectively regulating the diameter of the nanofibers, and enhancing the physical adsorption and electrostatic adsorption of particles by the nanofiber membrane during the air filtration process, and improving the filtration performance of the nanofiber membrane for fine particles in the air. The method is simple and efficient, has strong controllability, a wide range of applications, and is green and friendly. It avoids the problems of low resistance and high pressure drop in traditional nanofiber membranes in air filtration, and further expands the development and application of nanofiber membranes in the field of air filtration. It has important scientific significance and application value for nanofiber membranes in the fields of high temperature filtration and gas adsorption.
[0016] Furthermore, in step S1, the molar ratio of the diamine monomer to the dianhydride monomer is (0.95-1):(1-1.05); during the mixed reaction of the diamine monomer and the dianhydride monomer, the reaction temperature is 0-4°C and the reaction time is 24-28 h. This condition can reduce the heat generated in the reaction, increase the viscosity of the polyamic acid solution system, reduce the volatilization of the organic solvent, and the viscous polyamic acid solution is beneficial to the subsequent electrospinning process.
[0017] Furthermore, in step S1, the solvent replacement is specifically performed by slowly pouring the polyamic acid solution into water to solidify it, and washing it multiple times to complete the solvent replacement process, so that the residual solvent and water in the precipitated polyamic acid solid can be fully sublimated and the original structure of the polyamic acid solid can be maintained.
[0018] Furthermore, in step S2, the polar solvent is at least one of N,N'-dimethylformamide, N,N'-dimethylacetamide, N-methylpyrrolidone and tetrahydrofuran, which can accelerate the dissolution rate of the reaction monomer, facilitate the adjustment of the viscosity of the polyamic acid solution, and promote the condensation reaction.
[0019] Furthermore, the ionic liquid is one of 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate and 1-butyl-3-methylimidazolium hexafluorophosphate, which can increase a certain amount of charge in the polyamic acid spinning solution, making it easier to form nanofibers with smaller diameters during the electrospinning process.
[0020] Furthermore, after adding the ionic liquid, the mass concentration ratio of the ionic liquid to the polyamic acid spinning solution is (0.25%~1%):(36%~40%), which can make the nanofibers uniform during the electrospinning process, the prepared nanofiber membrane is flat and smooth, and the spinning solution has appropriate conductivity. The fibers are more easily stretched by the electric field during the spinning process, which helps to regulate the diameter of the fibers.
[0021] Furthermore, during the electrospinning process, the spinning voltage is 16 kV~18 kV, the flow rate of the spinning solution is 0.010~0.015 ml / min, and the distance between the needle and the receiving roller is 15~20 cm, which can make the fiber spinning uniform and stable, and the obtained nanofiber film has a suitable size.
[0022] Furthermore, the thermal imidization treatment is specifically as follows: heating to 150-170°C at a heating rate of 5°C / min, keeping warm for 30-60 min, then heating to 250-270°C at a heating rate of 5°C / min, keeping warm for 30-60 min, and finally heating to 300-320°C at a heating rate of 5°C / min, keeping warm for 30-60 min, so that the ionic liquid / polyamic acid nanofiber membrane can be completely converted into an ionic liquid / polyimide fiber membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0024] Figure 1The scanning electron microscope images and average fiber diameter images of the polyimide nanofiber membranes and ionic liquid / polyimide nanofiber membranes prepared in the comparative examples and Examples 1 to 4 of the present invention; Figure 2 The infrared spectra of the polyamic acid nanofiber membrane, polyimide nanofiber membrane and ionic liquid / polyimide nanofiber membrane prepared in the comparative example and Examples 1 to 4 of the present invention; Figure 3 Filtration efficiency diagram of polyimide nanofiber membrane and ionic liquid / polyimide nanofiber membrane prepared in comparative example and examples 1 to 4 of the present invention; Figure 4 The pressure drop diagrams of the polyimide nanofiber membrane and the ionic liquid / polyimide nanofiber membrane prepared in the comparative example and Examples 1 to 4 of the present invention; Figure 5 The quality factor diagrams of the polyimide nanofiber membrane and the ionic liquid / polyimide nanofiber membrane prepared in the comparative example and Examples 1 to 4 of the present invention. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0030] The present invention provides a method for preparing a polyimide nanofiber film modified by an ionic liquid, comprising the following steps: S1: A low-temperature polycondensation reaction is carried out using a diamine monomer and a dianhydride monomer to obtain a viscous polyamic acid solution, and then the polyamic acid solution is slowly poured into deionized water for solvent replacement, and then the solidified polyamic acid solid is freeze-dried and ground to obtain a yellow polyamic acid powder.
[0031] The diamine monomer is one of 4,4'-diaminodiphenyl ether (ODA), p-phenylenediamine (PPD) and m-phenylenediamine (MPD) or a mixture of any proportions thereof, which can make the polycondensation reaction stable and easy to control; The dianhydride monomer is one or a mixture of any proportion of pyromellitic anhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA), 3,3',4,4'-benzophenonetetracarboxylic anhydride (BTDA), which can make the polycondensation reaction stable and easy to control.
[0032] In the process of synthesizing the polyamic acid solution, the diamine monomer is first completely dissolved in a strong polar solvent, and then the dianhydride monomer is added in batches; each time the dianhydride monomer is added, the dianhydride monomer is completely dissolved before the next batch of dianhydride monomer is added.
[0033] The temperature of the polycondensation reaction is controlled at 0-4°C and the reaction time is 24-28 h. This condition can reduce the heat generated in the reaction, increase the viscosity of the polyamic acid solution system, reduce the volatilization of the organic solvent, and the viscous polyamic acid solution is beneficial to the subsequent electrospinning process.
[0034] The solvent replacement is to slowly pour the polyamic acid solution into deionized water to solidify, and wash it multiple times, and then freeze-dry it for 24 to 48 hours, so that the residual solvent and water in the precipitated polyamic acid solid can be fully sublimated and the original structure of the polyamic acid solid can be maintained.
[0035] The molar ratio of the diamine monomer to the dianhydride monomer is (0.95-1):(1-1.05).
[0036] S2: Under low temperature, the prepared polyamic acid powder is dissolved in a strong polar solvent and stirred until the polyamic acid powder is completely dissolved to obtain a polyamic acid spinning solution, and then a small amount of ionic liquid is added until the ionic liquid is completely dissolved to obtain an ionic liquid / polyamic acid spinning solution. The concentration of the polyamic acid spinning solution is 36 wt%~40 wt%. This condition can make the nanofibers uniform during the electrospinning process, and the obtained nanofiber membrane is flat and smooth.
[0037] The ionic liquid is one of 1-butyl-3-methylimidazolium chloride ([Bmim]Cl), 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim]BF4), and 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]PF6); the concentration of the ionic liquid added to the polyamic acid spinning solution is 0.25 wt%~1 wt%. This condition can make the spinning solution have appropriate conductivity, and the fiber is more susceptible to the stretching of the electric field during the spinning process, which helps to control the diameter of the fiber.
[0038] The strong polar solvent is one of N,N'-dimethylformamide (DMF), N,N'-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), tetrahydrofuran (THF) or a mixture of any proportions thereof.
[0039] The obtained ionic liquid / polyamic acid spinning solution is prepared into ionic liquid / polyamic acid nanofiber membrane through electrospinning technology. The spinning voltage of electrospinning is 16 kV~18 kV, the flow rate of the spinning solution is 0.010~0.015 ml / min, and the distance between the needle and the receiving roller is 15~20 cm, which can make the fiber spinning uniform and stable, and the obtained nanofiber film has a suitable size.
[0040] The obtained ionic liquid / polyamic acid nanofiber membrane is subjected to thermal imidization treatment, and the specific process is: heating to 150~170 ℃ at a heating rate of 5 ℃ / min, keeping warm for 30~60 min, then heating to 250~270 ℃ at a heating rate of 5 ℃ / min, keeping warm for 30~60 min, and finally heating to 300~320 ℃ at a heating rate of 5 ℃ / min, keeping warm for 30~60 min, which can completely convert the ionic liquid / polyamic acid nanofiber membrane into an ionic liquid / polyimide fiber membrane.
[0041] At the same time, the present invention also discloses a polyimide nanofiber film modified by an ionic liquid prepared by the above method, wherein the average diameter of the polyimide nanofiber modified by an ionic liquid is 200-350 nm; the average pore size of the polyimide nanofiber film modified by an ionic liquid is 10-25 nm; the quality factor of the polyimide nanofiber film modified by an ionic liquid is 0.022-0.74 Pa -1 .
[0042] In addition, the present invention also discloses an air purification filter comprising the above-mentioned ionic liquid-modified polyimide nanofiber film.
[0043] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0044] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0045] Comparative Example 1 Preparation of polyamic acid powder: According to the molar mass ratio of 4,4'-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) of 1:1.05, they were added to N,N'-dimethylformamide (DMF) solution and stirred at low temperature. The specific process was as follows: 100 mL of N,N'-dimethylformamide (DMF) solution was measured into a three-necked flask, and then 10 g of 4,4'-diaminodiphenyl ether (ODA) was weighed and added into the three-necked flask, and stirred and dissolved at a low temperature of 2 °C. After the solution was completely dissolved, 11.44 g of pyromellitic anhydride (PMDA) was weighed and added into the three-necked flask evenly in five times, each time with an interval of 15 min, and finally the inner wall of the three-necked flask was rinsed with 20 mL of N,N'-dimethylformamide (DMF), and the polyamic acid solution was obtained after stirring for 24 h. The polyamic acid solution was slowly poured into 3L of deionized water for solvent replacement, and the solid precipitated from the polyamic acid solution was washed several times, then soaked in deionized water for 4 hours to allow the polyamic acid solution to undergo sufficient solvent replacement. Finally, the solidified solid was placed in a refrigerator for pre-freezing for 8 hours, and then freeze-dried for 36 hours to obtain a polyamic acid solid, which was ground to obtain a polyamic acid powder (PAA).
[0046] Preparation of polyamic acid nanofiber membrane: Weigh 3 g of the above-mentioned polyamic acid powder and dissolve it in 5.163 mL of N,N'-dimethylformamide (DMF) solution. After stirring at low temperature for 4 h, a polyamic acid spinning solution with a mass concentration of 38 wt% is obtained, and the solution is placed in a refrigerator for defoaming. After complete defoaming, electrospinning is performed, the spinning voltage is set to 17 kV, the propulsion speed of the spinning solution is 0.012 ml / min, a 22G spinning needle is used, and the distance between the needle and the receiving roller is 15 cm to obtain a polyamic acid nanofiber membrane.
[0047] Preparation of polyimide nanofiber membrane: The above-mentioned nanofiber membrane was placed in a high-temperature tubular furnace for thermal imidization treatment, and N2 was introduced for staged heating. The specific heating program was as follows: heating to 160°C at a heating rate of 5°C / min, keeping warm for 30 min, then heating to 260°C at a heating rate of 5°C / min, keeping warm for 60 min, and finally heating to 310°C at a heating rate of 5°C / min, keeping warm for 30 min to obtain a polyimide nanofiber membrane (PI).
[0048] Example 1 Preparation of polyamic acid powder: 4,4'-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) were added to N,N'-dimethylformamide (DMF) solution according to a molar mass ratio of 1:1.05. Specifically, 100 mL of N,N'-dimethylformamide (DMF) solution was measured into a three-necked flask, and then 10 g of 4,4'-diaminodiphenyl ether (ODA) was weighed and added into the three-necked flask. The mixture was stirred and dissolved at a low temperature of 2 °C. After the mixture was completely dissolved, 11.44 g of pyromellitic anhydride (PMDA) was weighed and added into the three-necked flask in five equal portions, each time with an interval of 15 min. Finally, the inner wall of the three-necked flask was rinsed with 20 mL of N,N'-dimethylformamide (DMF), and the polyamic acid solution was obtained after stirring for 24 h. The polyamic acid solution was slowly poured into 3 L of deionized water for solvent replacement, and the solid precipitated from the polyamic acid solution was washed several times, then soaked in deionized water for 4 hours to allow the polyamic acid solution to undergo sufficient solvent replacement, and finally the solidified solid was placed in a refrigerator for pre-freezing for 8 hours, followed by freeze-drying for 36 hours to obtain a polyamic acid solid, which was ground to obtain a polyamic acid powder.
[0049] Preparation of ionic liquid / polyamic acid nanofiber membrane: 3 g of the above-mentioned polyamic acid powder was weighed and dissolved in 5.163 mL of N,N'-dimethylformamide (DMF) solution. After stirring at low temperature for 4 h, a polyamic acid spinning solution with a mass concentration of 38 wt% was obtained. Then, 0.25 wt% of ionic liquid 1-butyl-3-methylimidazolium chloride ([Bmim]Cl) was added and stirred for 2 h to obtain an ionic liquid / polyamic acid spinning solution, which was placed in a refrigerator for defoaming. After complete defoaming, electrospinning was performed, the spinning voltage was set to 17 kV, the propulsion speed of the spinning solution was set to 0.012 ml / min, a 22G spinning needle was used, and the distance between the needle and the receiving roller was 15 cm to obtain a polyamic acid nanofiber membrane.
[0050] Preparation of ionic liquid / polyimide nanofiber membrane: The above-mentioned nanofiber membrane was placed in a high-temperature tubular furnace for thermal imidization treatment, and N2 was introduced for staged heating. The specific heating program was as follows: heating to 160 °C at a heating rate of 5 °C / min, keeping warm for 30 min, then heating to 260 °C at a heating rate of 5 °C / min, keeping warm for 60 min, and finally heating to 310 °C at a heating rate of 5 °C / min, keeping warm for 30 min to obtain ionic liquid / polyimide nanofiber membrane (marked as 0.25 IL / PI).
[0051] Example 2 Preparation of polyamic acid powder: 4,4'-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) were added to N,N'-dimethylformamide (DMF) solution according to a molar mass ratio of 1:1.05. Specifically, 100 mL of N,N'-dimethylformamide (DMF) solution was measured into a three-necked flask, and then 10 g of 4,4'-diaminodiphenyl ether (ODA) was weighed and added into the three-necked flask. The mixture was stirred and dissolved at a low temperature of 2 °C. After the mixture was completely dissolved, 11.44 g of pyromellitic anhydride (PMDA) was weighed and added into the three-necked flask in five equal portions, each time with an interval of 15 min. Finally, the inner wall of the three-necked flask was rinsed with 20 mL of N,N'-dimethylformamide (DMF), and the polyamic acid solution was obtained after stirring for 24 h. The polyamic acid solution was slowly poured into 3 L of deionized water for solvent replacement, and the solid precipitated from the polyamic acid solution was washed several times, then soaked in deionized water for 4 hours to allow the polyamic acid solution to undergo sufficient solvent replacement, and finally the solidified solid was placed in a refrigerator for pre-freezing for 8 hours, followed by freeze-drying for 36 hours to obtain a polyamic acid solid, which was ground to obtain a polyamic acid powder.
[0052] Preparation of ionic liquid / polyamic acid nanofiber membrane: 3 g of the above-mentioned polyamic acid powder was weighed and dissolved in 5.163 mL of N,N'-dimethylformamide (DMF) solution. After stirring at low temperature for 4 h, a polyamic acid spinning solution with a mass concentration of 38 wt% was obtained. Then, 0.5 wt% of ionic liquid 1-butyl-3-methylimidazolium chloride ([Bmim]Cl) was added and stirred for 2 h to obtain an ionic liquid / polyamic acid spinning solution, which was placed in a refrigerator for defoaming. After complete defoaming, electrospinning was performed, the spinning voltage was set to 17 kV, the propulsion speed of the spinning solution was set to 0.012 ml / min, a 22G spinning needle was used, and the distance between the needle and the receiving roller was 15 cm to obtain a polyamic acid nanofiber membrane.
[0053] Preparation of ionic liquid / polyimide nanofiber membrane: The above-mentioned nanofiber membrane was placed in a high-temperature tubular furnace for thermal imidization treatment, and N2 was introduced for staged heating. The specific heating program was as follows: heating to 160 °C at a heating rate of 5 °C / min, keeping warm for 30 min, then heating to 260 °C at a heating rate of 5 °C / min, keeping warm for 60 min, and finally heating to 310 °C at a heating rate of 5 °C / min, keeping warm for 30 min to obtain ionic liquid / polyimide nanofiber membrane (marked as 0.5 IL / PI).
[0054] Example 3 Preparation of polyamic acid powder: 4,4'-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) were added to N,N'-dimethylformamide (DMF) solution according to a molar mass ratio of 1:1.05. Specifically, 100 mL of N,N'-dimethylformamide (DMF) solution was measured into a three-necked flask, and then 10 g of 4,4'-diaminodiphenyl ether (ODA) was weighed and added into the three-necked flask. The mixture was stirred and dissolved at a low temperature of 2 °C. After the mixture was completely dissolved, 11.44 g of pyromellitic anhydride (PMDA) was weighed and added into the three-necked flask in five equal portions, each time with an interval of 15 min. Finally, the inner wall of the three-necked flask was rinsed with 20 mL of N,N'-dimethylformamide (DMF), and the polyamic acid solution was obtained after stirring for 24 h. The polyamic acid solution was slowly poured into 3 L of deionized water for solvent replacement, and the solid precipitated from the polyamic acid solution was washed several times, then soaked in deionized water for 4 hours to allow the polyamic acid solution to undergo sufficient solvent replacement, and finally the solidified solid was placed in a refrigerator for pre-freezing for 8 hours, followed by freeze-drying for 36 hours to obtain a polyamic acid solid, which was ground to obtain a polyamic acid powder.
[0055] Preparation of ionic liquid / polyamic acid nanofiber membrane: Weigh 3 g of the above-mentioned polyamic acid powder and dissolve it in 5.163 mL of N,N'-dimethylformamide (DMF) solution. After stirring at low temperature for 4 h, a polyamic acid spinning solution with a mass concentration of 38 wt% is obtained. Continue to add ionic liquid 1-butyl-3-methylimidazolium chloride ([Bmim]Cl) with a mass concentration of 0.75 wt%, continue to stir for 2 h, and obtain an ionic liquid / polyamic acid spinning solution, which is placed in a refrigerator for defoaming. After complete defoaming, electrospinning is carried out, the spinning voltage is set to 17 kV, the propulsion speed of the spinning solution is 0.012 ml / min, a 22G spinning needle is used, and the distance between the needle and the receiving roller is 15 cm to obtain a polyamic acid nanofiber membrane.
[0056] Preparation of ionic liquid / polyimide nanofiber membrane: The above-mentioned nanofiber membrane was placed in a high-temperature tubular furnace for thermal imidization treatment, and N2 was introduced for staged heating. The specific heating program was as follows: heating to 160 °C at a heating rate of 5 °C / min, keeping warm for 30 min, then heating to 260 °C at a heating rate of 5 °C / min, keeping warm for 60 min, and finally heating to 310 °C at a heating rate of 5 °C / min, keeping warm for 30 min to obtain ionic liquid / polyimide nanofiber membrane (marked as 0.75 IL / PI).
[0057] Example 4 Preparation of polyamic acid powder: 4,4'-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) were added to N,N'-dimethylformamide (DMF) solution according to a molar mass ratio of 1:1.05. Specifically, 100 mL of N,N'-dimethylformamide (DMF) solution was measured into a three-necked flask, and then 10 g of 4,4'-diaminodiphenyl ether (ODA) was weighed and added into the three-necked flask. The mixture was stirred and dissolved at a low temperature of 2 °C. After the mixture was completely dissolved, 11.44 g of pyromellitic anhydride (PMDA) was weighed and added into the three-necked flask in five equal portions, each time with an interval of 15 min. Finally, the inner wall of the three-necked flask was rinsed with 20 mL of N,N'-dimethylformamide (DMF), and the polyamic acid solution was obtained after stirring for 24 h. The polyamic acid solution was slowly poured into 3 L of deionized water for solvent replacement, and the solid precipitated from the polyamic acid solution was washed several times, then soaked in deionized water for 4 hours to allow the polyamic acid solution to undergo sufficient solvent replacement, and finally the solidified solid was placed in a refrigerator for pre-freezing for 8 hours, followed by freeze-drying for 36 hours to obtain a polyamic acid solid, which was ground to obtain a polyamic acid powder.
[0058] Preparation of ionic liquid / polyamic acid nanofiber membrane: 3 g of the above-mentioned polyamic acid powder was weighed and dissolved in 5.163 mL of N,N'-dimethylformamide (DMF) solution. After stirring at low temperature for 4 h, a polyamic acid spinning solution with a mass concentration of 38 wt% was obtained. Then, 1 wt% of ionic liquid 1-butyl-3-methylimidazolium chloride ([Bmim]Cl) was added and stirred for 2 h to obtain an ionic liquid / polyamic acid spinning solution, which was placed in a refrigerator for defoaming. After complete defoaming, electrospinning was performed, the spinning voltage was set to 17 kV, the propulsion speed of the spinning solution was set to 0.012 ml / min, a 22G spinning needle was used, and the distance between the needle and the receiving roller was 15 cm to obtain a polyamic acid nanofiber membrane.
[0059] Preparation of ionic liquid / polyimide nanofiber membrane: The above-mentioned nanofiber membrane was placed in a high-temperature tubular furnace for thermal imidization treatment, and N2 was introduced for staged heating. The specific heating program was as follows: heating to 160 °C at a heating rate of 5 °C / min, keeping warm for 30 min, then heating to 260 °C at a heating rate of 5 °C / min, keeping warm for 60 min, and finally heating to 310 °C at a heating rate of 5 °C / min, keeping warm for 30 min to obtain ionic liquid / polyimide nanofiber membrane (marked as 1 IL / PI).
[0060] Furthermore, the technical solution of the present invention is explained through the accompanying drawings.
[0061] Figure 1The scanning electron microscope images of polyimide nanofiber membrane and ionic liquid / polyimide nanofiber membrane are shown in Figure 1. Figure 1 It can be seen that the diameter of the polyimide nanofibers without the addition of ionic liquid is larger, at 614nm. After adding the ionic liquid, the diameter of the ionic liquid / polyimide nanofibers is significantly reduced, with an average diameter of 257nm, indicating that the addition of ionic liquid can improve the overall conductivity of the spinning solution. The fibers are more susceptible to stretching by the electric field during the spinning process, which is beneficial to reducing the diameter of the fibers.
[0062] Figure 2 Infrared spectra of polyamic acid nanofiber membrane, polyimide nanofiber membrane and ionic liquid / polyimide nanofiber membrane. Figure 2 It can be seen that the polyamic acid nanofiber membrane has a -1 There is a broadband absorption peak at 1710cm -1 It is the absorption peak of amide I with -C=O; 1105cm -1 The absorption peak of the ether bond between the two benzene rings is at 1367cm. The broad absorption peaks of -NH and -COOH of polyamic acid in the polyimide nanofiber membrane disappear, and the absorption peaks at 1367cm -1 The CNC absorption peak of amide II band indicates that polyamic acid undergoes dehydration and cyclization to form polyimide nanofiber membrane after overheating imidization treatment; the ionic liquid / polyimide nanofiber membrane has a peak at 1558 cm -1 The absorption peak at is the vibration of the imidazole ring skeleton, indicating that the ionic liquid exists in the polyimide nanofibers.
[0063] Figures 3-5 The air filtration performance diagram of polyimide nanofiber membrane and ionic liquid / polyimide nanofiber membrane is shown in FIG. Figures 3-5 It can be seen that compared with polyimide nanofibers, the filtration efficiency of ionic liquid / polyimide nanofiber membrane for fine particles is improved, but at the same time the filtration resistance is also increased. The reason is that the addition of ionic liquid increases the charge density in the spinning solution. During the electrospinning process, the tensile force of the electric field on the fiber increases, thereby forming finer fibers; finer fibers tend to reduce the porosity of the nanofiber membrane, which is conducive to intercepting more fine particles, but it will also cause the problem of increased filtration resistance of the nanofiber membrane; According to the relationship between the filtration efficiency and filtration resistance of the nanofiber membrane, formula 1, the quality factor of the nanofiber membrane is calculated to judge the air filtration performance of the nanofiber membrane. When the addition content of ionic liquid increases to 0.75 wt%, the spinning solution system has an appropriate charge density and a higher quality factor, indicating that it has a higher filtration performance for fine particles. Specifically, the relationship between the filtration efficiency and filtration resistance of the nanofiber membrane is:
[0064] in, is the quality factor, is the filtration efficiency, When the air filter material has both high filtration efficiency and low resistance pressure drop, its quality factor value will be higher, which means it will have good filtration performance during use.
[0065] Example 5 A method for preparing a polyimide nanofiber film modified by an ionic liquid comprises the following steps: S1: Dissolve the diamine monomer completely in a strong polar solvent, and then add the dianhydride monomer in batches, dissolve the dianhydride monomer completely each time, and then continue to add the next batch of dianhydride monomer, react at 0°C for 28 hours to obtain a viscous polyamic acid solution, then slowly pour the polyamic acid solution into deionized water to solidify, and wash it several times until the polyamic acid solid is free of white solvent substances precipitated in the water, and there is no color change when immersed in water, and no tiny bubbles float in the water, and then freeze-dry the solidified polyamic acid solid for 24-48 hours, and grind it to obtain a yellow polyamic acid powder.
[0066] The diamine monomer is 4,4'-diaminodiphenyl ether (ODA), the dianhydride monomer is pyromellitic anhydride (PMDA), and the molar ratio of the diamine monomer to the dianhydride monomer is 0.95:1.
[0067] S2: Under low temperature environment, the prepared polyamic acid powder is dissolved in a strong polar solvent and stirred until the polyamic acid powder is completely dissolved to obtain a polyamic acid spinning solution with a concentration of 36 wt%, and then a small amount of ionic liquid is added until the ionic liquid is completely dissolved to obtain an ionic liquid / polyamic acid spinning solution.
[0068] The ionic liquid is 1-butyl-3-methylimidazolium chloride ([Bmim]Cl); the concentration of the ionic liquid added to the polyamic acid spinning solution is 0.25 wt%. The strong polar solvent is N,N'-dimethylformamide (DMF).
[0069] S3: The obtained ionic liquid / polyamic acid spinning solution is prepared into an ionic liquid / polyamic acid nanofiber membrane through electrospinning technology. The spinning voltage of electrospinning is 16 kV, the flow rate of the spinning solution is 0.010 ml / min, and the distance between the needle and the receiving roller is 15 cm, which can make the fiber spinning uniform and stable, and the obtained nanofiber film has a suitable size.
[0070] S4: The obtained ionic liquid / polyamic acid nanofiber membrane is subjected to thermal imidization treatment, and the specific process is: heating to 150°C at a heating rate of 5°C / min, keeping warm for 60 min, then heating to 250°C at a heating rate of 5°C / min, keeping warm for 60 min, and finally heating to 300°C at a heating rate of 5°C / min, keeping warm for 60 min, which can completely convert the ionic liquid / polyamic acid nanofiber membrane into an ionic liquid / polyimide fiber membrane.
[0071] In the ionic liquid modified polyimide nanofiber film prepared in this embodiment, the average diameter of the ionic liquid modified polyimide nanofiber is 200 nm; the average pore size of the ionic liquid modified polyimide nanofiber film is 25 nm; the quality factor of the ionic liquid modified polyimide nanofiber film is 0.022Pa -1 .
[0072] Example 6 A method for preparing a polyimide nanofiber film modified by an ionic liquid comprises the following steps: S1: Dissolve the diamine monomer completely in a strong polar solvent, and then add the dianhydride monomer in batches, dissolve the dianhydride monomer completely each time, and then continue to add the next batch of dianhydride monomer, react at 4°C for 24 hours to obtain a viscous polyamic acid solution, then slowly pour the polyamic acid solution into deionized water to solidify, and wash it several times until the polyamic acid solid is free of white solvent substances precipitated in the water, there is no color change when immersed in water, and no tiny bubbles float in the water, then freeze-dry the solidified polyamic acid solid for 48 hours, and grind it to obtain a yellow polyamic acid powder.
[0073] The diamine monomer is p-phenylenediamine (PPD), the dianhydride monomer is 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), and the molar ratio of the diamine monomer to the dianhydride monomer is 1:1.05.
[0074] S2: Under low temperature conditions, the prepared polyamic acid powder is dissolved in a strong polar solvent and stirred until the polyamic acid powder is completely dissolved to obtain a polyamic acid spinning solution with a concentration of 40 wt%, and then a small amount of ionic liquid is added until the ionic liquid is completely dissolved to obtain an ionic liquid / polyamic acid spinning solution.
[0075] The ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim]BF4); the concentration of the ionic liquid added to the polyamic acid spinning solution is 1 wt%. The strong polar solvent is N,N'-dimethylacetamide (DMAc).
[0076] S3: The obtained ionic liquid / polyamic acid spinning solution is prepared into an ionic liquid / polyamic acid nanofiber membrane through electrospinning technology. The spinning voltage of electrospinning is 18 kV, the flow rate of the spinning solution is 0.015 ml / min, and the distance between the needle and the receiving roller is 20 cm, which can make the fiber spinning uniform and stable, and the obtained nanofiber film has a suitable size.
[0077] S4: The obtained ionic liquid / polyamic acid nanofiber membrane is subjected to thermal imidization treatment, and the specific process is: heating to 170°C at a heating rate of 5°C / min, keeping warm for 30 min, then heating to 270°C at a heating rate of 5°C / min, keeping warm for 30 min, and finally heating to 320°C at a heating rate of 5°C / min, keeping warm for 30 min, which can completely convert the ionic liquid / polyamic acid nanofiber membrane into an ionic liquid / polyimide fiber membrane.
[0078] In the ionic liquid modified polyimide nanofiber film prepared in this embodiment, the average diameter of the ionic liquid modified polyimide nanofiber is 350 nm; the average pore size of the ionic liquid modified polyimide nanofiber film is 10 nm; the quality factor of the ionic liquid modified polyimide nanofiber film is 0.74 Pa -1 .
[0079] Example 7 A method for preparing a polyimide nanofiber film modified by an ionic liquid comprises the following steps: S1: Dissolve the diamine monomer completely in a strong polar solvent, and then add the dianhydride monomer in batches, dissolve the dianhydride monomer completely each time, and then continue to add the next batch of dianhydride monomer, react at 2°C for 25 hours to obtain a viscous polyamic acid solution, then slowly pour the polyamic acid solution into deionized water to solidify, and wash it several times until the polyamic acid solid is free of white solvent substances precipitated in the water, and there is no color change when immersed in water, and no tiny bubbles float in the water, then freeze-dry the solidified polyamic acid solid for 30 hours, and grind it to obtain a yellow polyamic acid powder.
[0080] The diamine monomer is meta-phenylenediamine (MPD), the dianhydride monomer is 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), and the molar ratio of the diamine monomer to the dianhydride monomer is 1:1.
[0081] S2: Under low temperature conditions, the prepared polyamic acid powder is dissolved in a strong polar solvent and stirred until the polyamic acid powder is completely dissolved to obtain a polyamic acid spinning solution with a concentration of 38 wt%, and then a small amount of ionic liquid is added until the ionic liquid is completely dissolved to obtain an ionic liquid / polyamic acid spinning solution.
[0082] The ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]PF6); the concentration of the ionic liquid added to the polyamic acid spinning solution is 0.5 wt%. The strong polar solvent is tetrahydrofuran (THF).
[0083] S3: The obtained ionic liquid / polyamic acid spinning solution is prepared into an ionic liquid / polyamic acid nanofiber membrane through electrospinning technology. The spinning voltage of electrospinning is 17 kV, the flow rate of the spinning solution is 0.012 ml / min, and the distance between the needle and the receiving roller is 18 cm, which can make the fiber spinning uniform and stable, and the obtained nanofiber film has a suitable size.
[0084] S4: The obtained ionic liquid / polyamic acid nanofiber membrane is subjected to thermal imidization treatment, and the specific process is: heating to 160°C at a heating rate of 5°C / min, keeping warm for 50 min, then heating to 260°C at a heating rate of 5°C / min, keeping warm for 40 min, and finally heating to 310°C at a heating rate of 5°C / min, keeping warm for 40 min, which can completely convert the ionic liquid / polyamic acid nanofiber membrane into an ionic liquid / polyimide fiber membrane.
[0085] In the ionic liquid modified polyimide nanofiber film prepared in this embodiment, the average diameter of the ionic liquid modified polyimide nanofiber is 300 nm; the average pore size of the ionic liquid modified polyimide nanofiber film is 15 nm; the quality factor of the ionic liquid modified polyimide nanofiber film is 0.5 Pa -1 .
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a polyimide nanofiber film modified by ionic liquid, characterized in that: The following steps are involved: S1: mixing a diamine monomer and a dianhydride monomer to react to obtain a polyamic acid solution, performing solvent replacement and freeze-drying to obtain a polyamic acid powder; S2: dissolving the polyamic acid powder in a polar solvent to obtain a polyamic acid spinning solution, and then adding an ionic liquid and stirring evenly to obtain an ionic liquid / polyamic acid spinning solution; S3: using the ionic liquid / polyamic acid spinning solution to perform electrospinning to obtain an ionic liquid / polyamic acid nanofiber membrane; S4: performing thermal imidization treatment on the ionic liquid / polyamic acid nanofiber membrane to obtain the ionic liquid modified polyimide nanofiber film.
2. The method for preparing a polyimide nanofiber film modified by ionic liquid according to claim 1, characterized in that: In step S1, the molar ratio of the diamine monomer to the dianhydride monomer is (0.95-1):(1-1.05); during the mixed reaction of the diamine monomer and the dianhydride monomer, the reaction temperature is 0-4° C. and the reaction time is 24-28 h.
3. The method for preparing a polyimide nanofiber film modified by ionic liquid according to claim 1, characterized in that: In step S1, the solvent replacement is specifically: slowly pouring the polyamic acid solution into water to solidify, and washing it multiple times to complete the solvent replacement process.
4. The method for preparing a polyimide nanofiber film modified by ionic liquid according to claim 1, characterized in that: In step S2, the polar solvent is at least one of N,N'-dimethylformamide, N,N'-dimethylacetamide, N-methylpyrrolidone and tetrahydrofuran.
5. The method for preparing a polyimide nanofiber film modified by ionic liquid according to claim 1, characterized in that: The ionic liquid is one of 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate and 1-butyl-3-methylimidazolium hexafluorophosphate.
6. The method for preparing a polyimide nanofiber film modified by ionic liquid according to claim 1, characterized in that: After the ionic liquid is added, the mass concentration ratio of the ionic liquid to the polyamic acid spinning solution is (0.25%~1%):(36%~40%).
7. The method for preparing a polyimide nanofiber film modified by ionic liquid according to claim 1, characterized in that: In the electrospinning process, the spinning voltage is 16 kV-18 kV, the flow rate of the spinning solution is 0.010-0.015 ml / min, and the distance between the needle and the receiving roller is 15-20 cm.
8. The method for preparing a polyimide nanofiber film modified by ionic liquid according to claim 1, characterized in that: The thermal imidization treatment is specifically as follows: heating to 150-170°C at a heating rate of 5°C / min, keeping warm for 30-60 min, then heating to 250-270°C at a heating rate of 5°C / min, keeping warm for 30-60 min, and finally heating to 300-320°C at a heating rate of 5°C / min, keeping warm for 30-60 min.
9. A polyimide nanofiber film modified by ionic liquid, characterized in that: The method according to any one of claims 1 to 8 is used to prepare the polyimide nanofiber film based on ionic liquid modification, wherein the average diameter of the polyimide nanofiber based on ionic liquid modification is 200 to 350 nm; the average pore size of the polyimide nanofiber film based on ionic liquid modification is 10 to 25 nm; the quality factor of the polyimide nanofiber film based on ionic liquid modification is 0.022 to 0.74 Pa -1 .
10. An air purification filter, characterized in that: The invention comprises a polyimide nanofiber film modified by ionic liquid as described in claim 9.
Citation Information
Patent Citations
High-strength polyimide nano fiber porous membrane, and preparation method and application thereof
CN103147253A
Polyimide paper / nanofiber composite membrane with double-layer filtration gradient as well as preparation method and application of polyimide paper / nanofiber composite membrane
CN116943448A
Cited By
Polyimide composite nanofiber membrane for lithium ion battery diaphragm and preparation method of polyimide composite nanofiber membrane
CN120384363A
Polyamide acid ionic liquid salt binder and lithium ion battery diaphragm
CN120904455A
Micro-nano integrated polyimide fiber cotton and water-soluble preparation method and application thereof
CN121204906A
Micro-nano integrated polyimide fiber cotton and water-soluble preparation method and application thereof
CN121204906B